Organizational Commitment of Professionals of a Chilean Municipal School: AMultidimensional Analysis According to Characterization Variables - Araya-Pizarro, Sebastián Cristóbal (2020)
The article analyzes the level of organizational commitment present in a public school in Chile, based on the sex, age, position and seniority of the employee. Through the application of the three-dimensional questionnaire of Organizational Commitment of Meyer and Allen(1991), to a sample of 60 collaborators, the presence of a level of moderate and homogeneous organizational commitment was revealed(affective commitment= 3.38, continuity commitment= 3.24, normative commitment= 3.19), finding only significant differences (p< 0.05) for the normative component according to the age of the official, who evidenced a higher level of moral commitment on the part of workers of greater age range[F(2, 57) = 7.88, p< 0.001]. It concludes about the need to establish transversal strategies that enhance emotional adhesion, the desire for permanence and reciprocity of officials towards the institution, which could be achieved through the generation of an organizational life plan, which manages to connect personal goals with those of the educational establishment.